2017
DOI: 10.1016/j.scitotenv.2016.10.202
|View full text |Cite
|
Sign up to set email alerts
|

Environmental challenges of the chlor-alkali production: Seeking answers from a life cycle approach

Abstract: Life Cycle Assessment (LCA) has been used to assess the environmental sustainability of the chlor-alkali production in Europe. The three current technologies applied nowadays are mercury, diaphragm, and membrane cell technology. Despite, having achieved higher energy efficiencies since the introduction of membrane technology, energy consumption is still one of the most important issues in this sector. An emerging technology namely oxygen-depolarised cathodes (ODC) is suggested as a promising approach for reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Since in the chlor-alkali sector there is no possibility of independently control the production of the three products, all the data and equations in the study are referred to the mixed tonne, which consists of 1 tonne of chlorine, 1.1 tonnes of caustic soda (sodium hydroxide) and 0.03 tonnes of hydrogen [20]. EEESA methodology comprises the four following steps (Figure 1): definition of the goal and scope, life cycle inventory (LCI) of the main consumptions and prices, energetic, economic and environmental impact assessment (EEEIA) and interpretation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since in the chlor-alkali sector there is no possibility of independently control the production of the three products, all the data and equations in the study are referred to the mixed tonne, which consists of 1 tonne of chlorine, 1.1 tonnes of caustic soda (sodium hydroxide) and 0.03 tonnes of hydrogen [20]. EEESA methodology comprises the four following steps (Figure 1): definition of the goal and scope, life cycle inventory (LCI) of the main consumptions and prices, energetic, economic and environmental impact assessment (EEEIA) and interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…An energetic, economic and environmental sustainability assessment will be conducted to study and compare the current available technologies to the emerging ODC technique. Several studies discussing the environmental sustainability of the chlor-alki sector were compiled in a previous work [20]. This bibliographic review of the state of the art showed the existing gap regarding the nexus energy-environment-economy of this energy demanding industry highlighting the novelty and interest of this paper.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Since electrolytic technologies can reduce energy consumption, the impacts of other stages, such as raw material extraction and production, become more significant (Garcia-Herrero et al, 2017). To assess the opportunities for integrating this novel technique into the chlor-alkali industry, the processing requirements of the cell itself must be considered in addition to the electricity requirements.…”
Section: Introductionmentioning
confidence: 99%